A distinct M2 macrophage infiltrate and transcriptomic profile decisively influence adipocyte differentiation in lipedema - Wolf, Stefan; Rannikko, Jenna H.; Virtakoivu, Reetta; Cinelli, Paolo; Felmerer, Gunther; Burger, Anna; Giovanoli, Pietro; Detmar, Michael; Lindenblatt, Nicole; Hollmén, Maija; Gousopoulos, Epameinondas (Frontiers in Immunology, 2022)
Lipedema is a chronic and progressive adipose tissue disorder, characterized by the painful and disproportionate increase of the subcutaneous fat in the lower and/or upper extremities. While distinct immune cell infiltration is a known hallmark of the disease, its role in the onset and development of lipedema remains unclear. To analyze the macrophage composition and involved signaling pathways, anatomically matched lipedema and control tissue samples were collected intra-operatively from gender- and BMI-matched patients, and the Stromal Vascular Fraction (SVF) was used for Cytometry by Time-of-Flight (CyTOF) and RNA sequencing. The phenotypic characterization of the immune component of lipedema versus control SVF using CyTOF revealed significantly increased numbers of CD163 macrophages. To gain further insight into this macrophage composition and molecular pathways, RNA sequencing of isolated CD11b+ cells was performed. The analysis suggested a significant modification of distinct gene ontology clusters in lipedema, including cytokine-mediated signaling activity, interleukin-1 receptor activity, extracellular matrix organization, and regulation of androgen receptor signaling. As distinct macrophage populations are known to affect adipose tissue differentiation and metabolism, we evaluated the effect of M2 to M1 macrophage polarization in lipedema using the selective PI3Kγ inhibitor IPI-549. Surprisingly, the differentiation of adipose tissue-derived stem cells with conditioned medium from IPI-549 treated SVF resulted in a significant decreased accumulation of lipids in lipedema versus control SVF. In conclusion, our results indicate that CD163+ macrophages are a critical component in lipedema and re-polarization of lipedema macrophages can normalize the differentiation of adipose-derived stem cells in vitro evaluated by the cellular lipid accumulation. These data open a new chapter in understanding lipedema pathophysiology and may indicate potential treatment options.